Analisis Butir Soal Pilihan Ganda Penilaian Akhir Semester pada Pembelajaran Tema 8 Praja Muda Karana Kelas III - Denna Delawanti; Yulianti Yulianti; Wildan Fajar Firdaus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Evaluation is often carried out after learning activities to assess the extent to which learning objectives have been achieved. The purpose of item analysis is to identify which questions are good, not so good, and which are bad. This research was carried out with the aim of analyzing multiple choice questions for the final semester assessment in learning theme 8 class III. This type of research is descriptive quantitative research. Sampling used a simple random sampling technique. The data collected was in the form of a final semester assessment of theme 8 learning for class III students at SDN 01 Putat Kidul, Malang Regency, totaling 12 students. Based on the results of the analysis of multiple choice questions in the Final Semester Assessment, it has been shown that: Theme 8 questions have a validity index with a